3D CFD analysis of a diamond lattice-based porous burner. (15th September 2020) - Billerot, Pierre-Lou; Dufresne, Louis; Lemaire, Romain; Seers, Patrice
Abstract: Innovative 3D metal and ceramic additive printing technologies allow manufacturing porous media with a tailored design pattern, unlike the sponge-like matrices commonly used in porous media burners. Based on this technology, this paper aims at modeling, at the pore scale, the flow behavior and combustion features within a structured diamond lattice pattern offering an isotropic and homogeneous porous medium as would be printed using additive manufacturing. A low porosity, 15 pores per inch, porous medium has been tested at equivalence ratios ranging from 0.55 to 0.8. Energy analysis of the proposed 3D model showed that solid radiation losses are negligible compared to solid conduction and convection. The heat transfer analysis reveals that the energy recirculation efficiency reaches a maximum value of 82% at lean-combustion regime. At the pore scale, a symmetrical flow pattern has been observed until a critical Reynolds number of 65 is reached. Based on the flow spatial variations, dispersion has been analyzed and compared with data reported in random structures. Using a lattice structure results in a more homogeneous energy release with less temperature spatial variations. This offers the advantage of decreasing thermal constraints associated with temperature gradients which induce breakage in random structure burners. Highlights: A 3D pore-resolved CFD model of a diamond lattice-based porous burner is proposed. The energy recirculation efficiency is maximized under lean-combustion regime. Flow pattern is symmetrical until the laminar nonlinear regime is reached. Diamond lattice-based porous burner results in a more homogeneous energy release. Spatial temperature variations are reduced and more homogeneous.